Efisiensi Pelayanan Administrasi Kependudukan Berbasis Identitas Digital : Analisis Integratif dalam Perspektif Nilai Islam di Provinsi Riau - Indrian Syafitri; Nurman Nurman; Annisa Mardatillah (Administratio, 2025)
The digital transformation of public services has become an urgent necessity, including in civil administration. This study analyzes the efficiency of administrative services through the implementation of the Digital Population Identity (Identitas Kependudukan Digital or IKD) in Riau Province, incorporating Islamic values as a distinctive evaluative and ethical framework in digital governance. Using a descriptive qualitative method with in-depth interviews, observation, and documentation, the findings reveal that IKD has improved service efficiency, reducing processing time from an average of 30 minutes to under 10 minutes per citizen. However, several challenges remain, including limited digital literacy, suboptimal inter-agency coordination, and low public awareness of data privacy. Islamic ethical principles such as amanah (trustworthiness), ihsan (excellence in conduct), and maslahah (public interest or common good) are applied as a normative and evaluative lens aligned with universal values such as integrity, professionalism, and public welfare. Unlike previous evaluations that focused primarily on technical or procedural aspects, this research uniquely integrates faith-based ethics into empirical assessment, offering broader relevance for digital ID initiatives in Muslim-majority contexts and developing nations. This study suggests enhancing digital literacy with value-based content, strengthening infrastructure, and institutionalizing Islamic ethical principles in digital public service policies to ensure trust, accountability, and sustainability.